Wolfram syndrome with vitelliform retinal deposits. (2nd January 2022) - Sabet, Sina J.; Carey, Andrew R.
ABSTRACT: Background: : Wolfram Syndrome is a rare genetic disorder usually inherited in an autosomal recessive manner. The acronym DIDMOAD characterizes the classic constellation of findings: diabetes insipidus, diabetes mellitus, optic atrophy, and deafness. However, other ocular and systemic manifestations may also be present. The aim of this report is to present a patient with Wolfram Syndrome presenting with vitelliform changes in the retina – an association that has not been previously reported. Materials and Methods: : Case Report Results: : Ophthalmologic examination and imaging studies showed bilateral optic neuropathy and scattered bilateral subretinal vitelliform deposits. Genetic testing was positive for Wolfram Syndrome. Conclusion: : This patient showed optic atrophy with associated vitelliform retinal changes. The previously unreported association of these findings present possible associations in the molecular pathophysiology underlying both Wolfram syndrome and the spectrum of retinal disorders associated with vitelliform changes.